Endothelial cells sialylate IgG within the FcRn-mediated recycling pathway - Leandre M. Glendenning; Megan D. Long; Gracie C. Carlson; Austin D. Silva; Siyu Wang; Kalob M. Reynero; Emily N. Kukan; Susan L. Bellis; Wendy A. Goodman; Brian A. Cobb (Proceedings of the National Academy of Sciences, 2025)
IgG is a key to adaptive immunity and a critical platform for drug design. Sialic acid on the conserved glycan within the Fc domain is believed to promote anti-inflammatory IgG function; however, regulation of sialylation remains poorly defined. We previously showed that IgG sialylation is primarily mediated by B cell–extrinsic processes in mice. Here, we found that IgG sialylation occurs in the subcellular compartments of the FcRn-mediated IgG recycling pathway of endothelial cells. This process is down-regulated by inflammatory signals and up-regulated during gestation, providing mechanistic insight into the epidemiology associating IgG glycosylation, pregnancy and inflammatory disease. These findings demonstrate that plasma-localized IgG glycosylation is dynamically altered by the endothelium, revealing a potential mechanism through which the function of all endogenous and administered IgG and Fc-containing pharmaceuticals could be altered.